KEUANGAN NEGARA DALAM ISLAM (MELACAK SUMBER-SUMBER PENDAPATAN DAN PENGELUARAN NEGARA) - Asyari, Asyari (Alhurriyah, 2009)
This article discusses public finance, one of studies in Islamic economics, in history perspective from prior of Prophetic to Khalifaurasyidin. That time is supposed as operated Islamic State (Daulah Islamiyyah) efectively . From history noticed that zakat, ghanimah, fai, jizyah, kharaj, ‘ushur, dharimah and waqf as wel as shadakah are nation of Islamic income. Before distributing to ummat, all of them organized by baitul maal. Nation of Islamic expenditures are spending to develop public facilities or to reduce proverty, war, education, propagantion (dakwah) and development of religion in society. Conclution of this discusses that the characteristic of nation of Islamic expenditure is not only to reach society peaceful on material aspect but also to develop society based on spritual.